PWE-062 Fructose Intolerance in Pelvic Radiation Disease; Is It More Common than We Realised?. (17th August 2016) - Stacey, R; Langasco, N; Ludlow, H; Turner, J; Green, J
Abstract : Introduction: Guidelines have recently been published regarding the management of Pelvic Radiation Disease (PRD) and late effects of cancer care. 1 The guidelines have been shown in peer reviewed studies to be effective in the management of PRD. 2 The guidelines include a number of investigations for certain symptoms and include carbohydrate tolerance tests for substrates such as fructose. That said there are currently no published case series or studies evaluating the prevalence and diagnostic yield of fructose breath testing in PRD. We have recently set up a dedicated late effects of cancer care and pelvic radiation disease clinic in Cardiff and audited the results of our fructose tolerance breath tests. Patients with diarrhoea, bloating or abdominal pain were investigated with fructose breath testing as per these guidelines. Methods: We audited the results for all fructose breath tests in 2014 in patients with suspected PRD via a database search and correlation with clinical notes. Total of 82 patients were identified as having a fructose breath tests in the 1 year period) 20 of which were being investigated for suspected PRD. (10 Male, 10 female, median age 65.5) Results: 45% of fructose breath tests in patients with suspected PRD were positive (n = 9) All of these patients were referred with either diarrhoea, bloating or abdominal pain. Of these patients with positive tests, 44% were found to have a dual pathology (n = 4) with other diagnoses including small intestinal bacterial overgrowth, lactose intolerance and bile acid diarrhoea. Conclusion: Fructose intolerance is common in patients with diarrhoea, bloating and abdominal pain in PRD. The diagnostic yield of testing is high and should be considered as a differential diagnosis in these patients. It is important to recognise that dual pathology frequently occurs and that an algorithmic approach is useful in these patients. References: 1 Andreyev HJN, Muls AC, Norton C, Ralph C, Watson L, Shaw C, et al . Guidance: The practical management of the gastrointestinal symptoms of pelvic radiation disease. Frontline Gastroenterology [Internet]. BMJ Publishing Group Ltd; 2014 Jun 17;flgastro–2014–100468. Available from: http://fg.bmj.com/content/early/2014/06/17/flgastro-2014-100468.abstract 2 Andreyev HJN, Benton BE, Lalji A, Norton PC, Kabir M, GaugeGage PH, et al . ArticlesAlgorithm-based management of patients with gastrointestinal symptoms in patients after pelvic radiation treatment (ORBIT): a randomised controlled trial. Lancet. Elsevier Ltd; 2013 Sep 20;1–9. Disclosure of Interest: None Declared